ERα Signaling Increased IL-17A Production in Th17 Cells by Upregulating IL-23R Expression, Mitochondrial Respiration, and Proliferation - Fuseini, Hubaida; Cephus, Jacqueline-Yvonne; Wu, Pingsheng; Davis, J. Brooke; Contreras, Diana C.; Gandhi, Vivek D.; Rathmell, Jeffrey C.; Newcomb, Dawn C. (Frontiers in Immunology, 2019)
Women have increased prevalence of Th17-mediated autoimmune diseases, including lupus and multiple sclerosis, and severe asthma. While estradiol and progesterone increased IL-17A production in Th17 cells by inhibiting Let7f miRNA expression and increasing IL-23 receptor (IL-23R) expression, it remained unclear how estrogen signaling through the canonical nuclear receptors, estrogen receptor α (ERα) and/or ERβ, regulated this pathway. We hypothesized that estrogen signaling through ERα increased IL-23R expression and IL-17A production from Th17 cells. To test this hypothesis, naïve T cells from WT female, WT male, Esr1-/- and Esr2-/- female mice were differentiated into Th17 cells. IL-17A production and IL-23R expression were significantly increased in Th17 cells from WT female mice compared to Th17 cells from WT male mice. Deletion of ERα (Esr1-/-), but not ERβ (Esr2-/-), significantly decreased IL-17A production and IL-23R expression in Th17 cells by limiting IL-23R expression in a Let-7f dependent manner. ERα deficiency also decreased Th17 cell proliferation as well as decreased T cell metabolism as measured by ATP-linked oxygen consumption rate and proton leakage. Further, we found that Cox20 expression, a protein involved in mitochondrial respiration through assembly of cytochrome c oxidase in the electron transport chain, was increased in Th17 cells from WT female mice compared to Th17 cells from WT male and Esr1-/- female mice. Inhibition of Cox20 decreased IL-17 production in Th17 cells from WT female mice. Combined these studies showed that ERα signaling increased IL-17A production in Th17 cells by upregulating IL-23R expression and promoting mitochondrial respiration and proliferation.